Pengaruh Senam Asma Terhadap Kekambuhan pada Penderita Asma di Wilayah Kerja Puskesmas Muka Kabupaten Cianjur - Dewi, Sri Kurnia; Lutiyah, Lutiyah; Martini, Eva; Hamidah, Ernawati; Alamsyah, Azhar Zulkarnain; Feresia, Shinta; Salsabila, Salwa (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT  Asthma gymnastics is a type of exercise therapy that is carried out in groups (exercise groups) involving body movement activities or is an essential activity to assist the respiratory rehabilitation process in asthma sufferers and is one of the supporting elements in asthma treatment. Asthma is a lung disease with the following characteristics: airways that are reversible (but incomplete in some patients) spontaneously or with treatment; airway inflammation; Increased airway response to various stimuli (hyperactivity). This study aims to determine whether asthma exercise can reduce the frequency of recurrences in the Working Area of the Muka Public Health Center Cianjur. The method used in this research is experimental research with the research design used is the Pre and Post Test with Control Group Design. The sample of this study were 30 people with asthma, 15 people with asthma were used as the treatment group and 15 people with asthma were used as the control group, selected randomly. This study showed that the treatment group experienced an increase in well-controlled relapses and decreased uncontrolled relapses. Based on the Mann Whitney test, a p value = 0.008 was obtained, this means that asthma exercise can reduce recurrence in bronchial asthma patients. The conclusion of this study states that giving asthma exercise training three times a week for eight weeks can reduce the frequency of recurrences and increase oxygen saturation in asthma sufferers. Asthma exercise is expected to be carried out by asthma sufferers on a regular basis in an effort to control the frequency of asthma attacks effectively. The conclusion of this study states that giving asthma exercise training three times a week for eight weeks can reduce the frequency of recurrences and increase oxygen saturation in asthma sufferers. Asthma exercise is expected to be carried out by asthma sufferers on a regular basis in an effort to control the frequency of asthma attacks effectively. Keywords: Asthma Exercise, Recurrence Frequency, Asthma Sufferers  ABSTRAK Senam Asma adalah salah satu jenis terapi latihan yang dilakukan secara berkelompok (exercise group) yang melibatkan aktifitas gerakan tubuh atau merupakan kegiatan esensial untuk membantu proses rehabilitasi pernafasan pada penderita asma dan merupakan salah satu bagian penunjang terapi asma. Penyakit asma adalah penyakit paru dengan karakteristik : saluran napas yang reversible (tetapi tidak lengkap pada beberapa pasien) secara spontan maupun pengobatan; Inflamasi saluran napas; Peningkatan respons saluran napas terhadap berbagai rangsangan (hipereaktivitas). Penelitian ini bertujuan untuk mengetahui apakah senam asma dapat mengurangi frekuensi kekambuhan di Wilayah Kerja Puskesmas Muka Kabupaten Cianjur. Metode yang dipakai pada penelitian ini adalah penelitian eksperimental dengan  rancangan  penelitian yang digunakan adalah Pre and Post Test with Control Group Design. Sampel penelitian ini adalah 30 orang penderita asma, 15 orang penderita asma dijadikan kelompok perlakuan dan 15 orang penderita asma dijadikan kelompok kontrol dipilih secara random”. Menunjukkan bahwa kelompok perlakuan mengalami peningkatan kekambuhan terkontrol baik dan mengalami penurunan kekambuhan tidak terkontrol. Berdasarkan uji Mann Whitney diperoleh nilai p = 0,008, hal ini berarti senam asma dapat mengurangi kekambuhan pada pasien asma bronkiale. Menyatakan bahwa pemberian pelatihan senam asma dilakukan tiga kali seminggu selama delapan minggu mampu menurunkan frekuensi kekambuhan dan meningkatkan saturasi oksigen pada penderita asma. Senam asma diharapkan dapat dilaksanakan secara rutin guna mengontrol frekuensi serangan asma secara efektif”. Kata Kunci: Senam Asma, Frekuensi Kekambuhan, Penderita Asma